Criterios generales para influir sobre los precios internos de los artículos de consumo - Spinelli, Armando P. (1957)
The economic policy of the country lacks the necessary norms to protect the local consumption. While it is true that the government has to continue its efforts to sell the country's products on the international market at the highest possible prices, it is not less true that it has the duty to create a mechanism able to intervene and neutralize the pernicious effects which its economic policy could have on the internal prices, as the local consumer has to pay the same high prices our crops and meat could obtain on the international market. Analysing the special case of the meat, the author expresses his thoughts in sketching the outlines of a bill which should lead to this effect.